(untitled) (Research, Society and Development, 2023)
Structural monitoring significantly contributes to greater and better knowledge of the real behavior of structures, having positive consequences both from an economic and social point of view. Currently, observation and monitoring is increasingly based on measurement systems that are an integral part of the structure. Sustainable engineering is something we have to keep in mind throughout the project, from planning and design to execution and operation. The Article will also mention 10 guidelines from the National Directive on Sustainable Development and Environmental Management of Professional Engineers, which was produced by Engineers Canada in 2016. The aim of these guidelines is to encourage Engineers to be proactive in protecting and managing a responsible environment. part inherent to the duties assumed by all engineers: researchers, academics, consultants, regulators or managers.